SYNTHESIS OF POLY(ACRYLAMIDE-CO-ACRYLIC ACID)-STARCH BASED SUPERABSORBENT HYDROGELS BY GAMMA RADIATION: STUDY ITS SWELLING BEHAVIOR - Erizal Erizal (Indonesian Journal of Chemistry, 2012)
Modification of poly (acrylamide-co-acrylic acid) superabsorbent hydrogels with varying starch concentration (1-3%) via simultaneous gamma radiation have been carried out. The structure and morphology of copolymers were characterization by Fourier transform infra red spectroscopy and scanning electron microscopy. The gel fraction, swelling kinetics and the equilibrium degree of swelling (EDS) of the hydrogels were studied. It was found that the an increase in the starch content present in the hydrogels (1-3%) and with increase irradiation dose  from 10 kGy up to 30 kGy, the swelling ratio decreased from 250-100 g/g. Incorporation of 1% starch increases the EDS of the hydrogels up 350 g/g. Under maximum conditions, poly(AAm-co-AA)-starch hydrogels with high gel fraction (~93%) was prepared from aqueous solution containing 5% AAm, 15% acrylic acid and 0-3% starch. The hydrogels were sensitive against salts solution.